2018
DOI: 10.1029/2018jf004617
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Loss Affects Tides and the Sediment Budget in Shallow Bays

Abstract: The current paradigm is that salt marshes and their important ecosystem services are threatened by global climate change; indeed, large marsh losses have been documented worldwide. Morphological changes associated with salt marsh erosion are expected to influence the hydrodynamics and sediment dynamics of coastal systems. Here the influence of salt marsh erosion on the tidal hydrodynamics and sediment storage capability of shallow bays is investigated. Hydrodynamics, sediment transport, and vegetation dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 75 publications
9
49
0
Order By: Relevance
“…The dynamical system approach is very powerful and should be extended to include novel schematizations of the marsh system. The general pathway to create such models is based on four steps: (1) the use of highly detailed hydrodynamic models to identify feedbacks (e.g., Donatelli et al, 2018; Mariotti et al, 2010), (2) the schematization and aggregation of the system into geometric compartments (i.e., points), (3) the formulation of simplified, yet mass conserving, fluxes between the compartments, and (4) the inclusion of all external inputs and outputs of sediment.…”
Section: Nonlinear Dynamics and Stability Analysis Applied To Salt Mamentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamical system approach is very powerful and should be extended to include novel schematizations of the marsh system. The general pathway to create such models is based on four steps: (1) the use of highly detailed hydrodynamic models to identify feedbacks (e.g., Donatelli et al, 2018; Mariotti et al, 2010), (2) the schematization and aggregation of the system into geometric compartments (i.e., points), (3) the formulation of simplified, yet mass conserving, fluxes between the compartments, and (4) the inclusion of all external inputs and outputs of sediment.…”
Section: Nonlinear Dynamics and Stability Analysis Applied To Salt Mamentioning
confidence: 99%
“…Ganju et al (2017) have shown that the sediment budget of the marsh‐tidal flat complex scales with the unvegetated/vegetated marsh ratio of the estuarine system, suggesting that this metric can be used as an indicator of marsh vulnerability. However, the external inputs and outputs of sediment are not the only factors influencing the marsh capability to retain sediments, and the sediment dynamics within the marsh complex can also cause spatial and temporal variability in the sediment budget (e.g., Donatelli et al, 2018, 2019; Li & Yang, 2009; Mei et al, 2016; Temmerman et al, 2005; Zhang et al, 2019).…”
Section: Assessment Of Marsh Vulnerability and Resilience Through Sedmentioning
confidence: 99%
See 1 more Smart Citation
“…This asymmetry, that strongly depends on the bathymetry, can produce flood periods shorter than ebb periods, and flood velocities larger than ebb velocities [42,86,94]. The areas with the highest variation in tidal amplitude are frequently the ones where geometric variations associated with marsh loss are more pronounced [95].…”
Section: Tidal Asymmetrymentioning
confidence: 99%
“…Erosive cliffs continue south and give rise to a relatively smooth shoreline profile. Marsh areas and vegetated surfaces can be especially relevant for the mitigation of extreme water levels [46][47][48][49]. Five major nesses, i.e., projections originating from sandy deposits, are then present along the coast at Winterton (around 52.72N, 1.7E), Caister (52.62N, 1.74E), Lowestoft (52.48N, 1.76E), Benacre (52.38N, 1.71E) and Thorpeness (52.17N, 1.61E) [50].…”
Section: Study Sitementioning
confidence: 99%